Locally Expansive Solutions for a Class of Iterative Equations - Wei Song; Sheng Chen (The Scientific World Journal)
Iterative equations which can be expressed by the following form fnx=Hx,fx,f2x,…,fn−1x, where n≥2, are investigated. Conditions for the existence of locally expansive C1 solutions for such equations are given.